PARADIGMA DASAR FENOMENOLOGIS, HERMENEUTIKA DAN TEORI KRITIS - Wisri Wisri; Abd. Mughni (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
Attempts to understand reality as it exists in its purity without the need to "intervention" by anything and anyone. Regardless of that advantages and disadvantages, that has provided a valuable contribution to the world of science, overcoming the crisis of methodology, and could become an influential discipline. Phenomenology tries to come near to the object of the study critically and carefully in observation, by not prejudiced with any previous conceptions. Therefore, it is seen as a rigorous science (a tight science) by the phenomenologist. Hermeneutic initially "only" interpret the texts of holy book, in the development becoming more expansive. It spread abroad to the other fields in the social sciences, especially philology, dassein and existential understanding, interpretation, and interpretation system. Finally phenomenology and hermeneutic can be firmly united by Ricoeur. They reputed that they can not be separated and should be accompanied each other. Phenomenology is a basic "irreplaceable" assumption for hermeneutic. On the contrary, hermeneutic is the proponent for phenomenology to running the program well. While the goal of critical theory is to eliminate the various forms of domination and encourage freedom, justice and equality. This theory uses the reflective method by getting constructive critisism to the social administration or institution, politic or economic, which tended to obstructive to the attainment of freedom, justice, and equality.